3(q+4)-10q=2q+3

Simple and best practice solution for 3(q+4)-10q=2q+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(q+4)-10q=2q+3 equation:


Simplifying
3(q + 4) + -10q = 2q + 3

Reorder the terms:
3(4 + q) + -10q = 2q + 3
(4 * 3 + q * 3) + -10q = 2q + 3
(12 + 3q) + -10q = 2q + 3

Combine like terms: 3q + -10q = -7q
12 + -7q = 2q + 3

Reorder the terms:
12 + -7q = 3 + 2q

Solving
12 + -7q = 3 + 2q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-2q' to each side of the equation.
12 + -7q + -2q = 3 + 2q + -2q

Combine like terms: -7q + -2q = -9q
12 + -9q = 3 + 2q + -2q

Combine like terms: 2q + -2q = 0
12 + -9q = 3 + 0
12 + -9q = 3

Add '-12' to each side of the equation.
12 + -12 + -9q = 3 + -12

Combine like terms: 12 + -12 = 0
0 + -9q = 3 + -12
-9q = 3 + -12

Combine like terms: 3 + -12 = -9
-9q = -9

Divide each side by '-9'.
q = 1

Simplifying
q = 1

See similar equations:

| 2x+3x+5=5(2x-3) | | 4z-2(z+6)=7z+8 | | 5x^2-30x-80= | | 6y+2y=9-3y | | 2x-5x=5+4y | | 5x-x+7x= | | 3x+2=5-x | | 2x=3x-2 | | 502.4=12(3.141592654)(r)+(3.141592654)(r^2) | | 4p^2q+q^3-q^2=0 | | 502.4=12(pi)(r)+(pi)(r^2) | | 4-2n=5n+n | | 33=P(0.06)3 | | 6+2n=4n-3n | | 8v+1=7v-2-0 | | 9-(4y-9)=8-5y | | -21c+19=21c-1 | | -36+3x^2=0 | | 3x^2*x=108 | | 18=15-n+3 | | 0.5(6x+12)=1.3-(x+2) | | 6x-y=17 | | 2-2n=n+15 | | -20=10-6+n | | -16=5+n | | 6(3-2z)+13z-4= | | 4+3n=1-4n | | 36+p-4=p | | 3x-9=x+4 | | v(v+1)=272 | | 2-8v=2v+8 | | =6x^2+5xy-25y^2 |

Equations solver categories